Dynamics of Individual T Cell Repertoires: From Cord Blood to Centenarians - Britanova, Olga V; Shugay, Mikhail; Merzlyak, Ekaterina M; Staroverov, Dmitriy B; Putintseva, Ekaterina V; Turchaninova, Maria A; Mamedov, Ilgar Z; Pogorelyy, Mikhail V; Bolotin, Dmitriy A; Izraelson, Mark; Davydov, Alexey N; Egorov, Evgeny S; et al. (Journal of immunology (Baltimore, Md., 2016)
The diversity, architecture, and dynamics of the TCR repertoire largely determine our ability to effectively withstand infections and malignancies with minimal mistargeting of immune responses. In this study, we have employed deep TCRβ repertoire sequencing with normalization based on unique molecular identifiers to explore the long-term dynamics of T cell immunity. We demonstrate remarkable stability of repertoire, where approximately half of all T cells in peripheral blood are represented by clones that persist and generally preserve their frequencies for 3 y. We further characterize the extremes of lifelong TCR repertoire evolution, analyzing samples ranging from umbilical cord blood to centenarian peripheral blood. We show that the fetal TCR repertoire, albeit structurally maintained within regulated borders due to the lower numbers of randomly added nucleotides, is not limited with respect to observed functional diversity. We reveal decreased efficiency of nonsense-mediated mRNA decay in umbilical cord blood, which may reflect specific regulatory mechanisms in development. Furthermore, we demonstrate that human TCR repertoires are functionally more similar at birth but diverge during life, and we track the lifelong behavior of CMV- and EBV-specific T cell clonotypes. Finally, we reveal gender differences in dynamics of TCR diversity constriction, which come to naught in the oldest age. Based on our data, we propose a more general explanation for the previous observations on the relationships between longevity and immunity.
Keywords: fetální krev; lidé; mladiství; software; Adult; Middle Aged; buněčné klony; simulace molekulární dynamiky; stárnutí; imunodominantní epitopy; Receptors, Antigen, T-Cell, alpha-beta; Longevity; Female; dítě; receptory antigenů T-buněk alfa-beta; Adolescent; Humans; Clone Cells; Software; T-lymfocyty; Immunodominant Epitopes; lidé středního věku; T-Lymphocytes; mužské pohlaví; mladý dospělý; Time Factors; dlouhověkost; ženské pohlaví; Young Adult; Aging; Aged, 80 and over; senioři nad 80 let; časové faktory; Aged; Male; Molecular Dynamics Simulation; Child; dospělí; Fetal Blood; senioři